Media Realita Meningkatkan Hasil Belajar Bentuk dan Wujud Benda pada Siswa Kelas II SDN 31 Gedong Tataan, Kecamatan Gedong Tataan Tahun 2019 - Teguh Rahayu (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
The background of this research is that the activities and learning outcomes of science students in grade II at SDN 31 Gedong Tataan are still low. The research was conducted with the aim of increasing learning activities and learning outcomes by using reality media. This type of research is action research which is carried out reflectively and collaboratively for three cycles. The subjects of this study were 14 grade II students at SDN 31 Gedong Tataan for the 2019/2020 academic year. The results of the analysis of student activity data increased. In the first cycle of 62.5%, the second cycle of 75% to 87.5% in the third cycle. Likewise, student learning outcomes showed an increase from an average of 62.85 in the first cycle, to 72.42 in the second cycle and to 82.75 in the third cycle. Based on the results of this study it can be concluded that the use of reality media can increase the activity and learning outcomes of class II students at SDN 31 Gedong Tataan, Gedong Tataan District, Pesawaran Regency.